The peroxins BcPex8, BcPex10, and BcPex12 are required for the development and pathogenicity of Botrytis cinerea - Li, Ling; Yu, Meng-xue; Guo, Jian; Hao, Zhong-na; Zhang, Zhen; Lu, Zi-qi; Wang, Jiao-yu; Zhu, Xue-ming; Wang, Yan-li; Chen, Jie; Sun, Guo-Chang; Lin, Fu-cheng (Frontiers in Microbiology, 2022)
Peroxisomes have been proved playing roles in infection of several plant pathogens. Although the contribution of a portion of peroxins in pathogenicity was demonstrated, most of them are undocumented in fungi, especially, Botrytis cinerea. The homologues of Pex8, Pex10 and Pex12 in B. cinerea were functionally characterized in this work by using gene disruption strategies. Compared with the wild type strain, the ∆bcpex8, ∆bcpex10 and ∆bcpex12 mutants exhibited significant reduction in melanin production, fatty acid utilization and aerial mycelia growth, decreased tolerance to high osmotic pressure and reactive oxygen species (ROS), and a delay in conidial germination, germ tube elongation as well as a decrease formation rate of initiate infection structure (IFSs). The pathogenicity was tested on the leaves of tobacco and strawberry, and fruits of tomato. On the leaves of tobacco and strawberry, the ∆bcpex8, ∆bcpex10 and ∆bcpex12 mutants could not induce necrotic lesions, and the lesions on tomato fruits infected with the mutants were significant reduced than those of the wide type. The results indicated that BcPEX8, BcPEX10 and BcPEX12 are indispensable for the development and pathogenicity of B. cinerea.